Resilient, recovering, distressed: A longitudinal qualitative study of parent psychosocial trajectories following child critical injury. Issue 10 (October 2019) - Foster, Kim; Mitchell, Rebecca; Van, Connie; Young, Alexandra; McCloughen, Andrea; Curtis, Kate
Highlights: Parents of injured children are at substantial risk of developing adverse mental health outcomes. Three parent trajectory patterns of parent experience were identified; resilient; recovering ; and distressed . A dedicated trauma support role can facilitate an integrated care approach for families across the injury care continuum. Abstract: Introduction: The psychological distress and risk of mental health problems for parents of children with critical injury is well-established. There has been little exploration, however, of parent experiences and psychosocial trajectories over time following child critical injury. To address this knowledge gap, a longitudinal qualitative study was conducted to explore parent experiences and support needs and identify parent psychosocial trajectories in the 12 months following child critical injury. Methods: Semi- structured in-depth interviews were conducted with 27 parents at three time points over a 12 month period: the immediate hospital period post-child injury, and 6 and 12 months following injury, resulting in a total of 81 interviews. Data were analysed using a longitudinal within and across-case thematic analysis of patterns emerging over time. Findings: Three parent trajectory patterns were identified: resilient trajectory where parents were temporarily disrupted by the child's injury and hospitalisation, but recovered their mental and emotional wellbeing quickly, which was maintained over time; recovering trajectory where parents were initially disrupted at the time of injury but their mental and emotional wellbeing fluctuated over time and had not been fully restored by 12 months; and distressed trajectory where parents experienced significant psychosocial disruption due to their child's injury and struggled to adapt and regain their wellbeing over time, remaining emotionally distressed about the circumstances and impacts of the injury on their child and family. Illustrative narratives that represent each trajectory are presented. Conclusions: This is the first qualitative study to report the psychosocial trajectories of parents of critically injured children. Clinical application of insights provided by these trajectories can assist clinicians to use targeted strategies to help strengthen parental adaptation and prevent adverse mental health outcomes, and address families' psychosocial support needs following child injury. Screening for parent psychological distress and post-traumatic stress disorder is needed from the time of the child's admission, and a dedicated trauma support role can facilitate an integrated care approach for children and families with complex needs across the care continuum.